Effect of drug properties on physical and release characteristics of Eudragit microspheres prepared by spherical crystallization technique - (:unkn) unknown (MARCEL DEKKER INC, 1997)
Ten compounds having different solubilities and molecular weights were evaluated for incorporation into Eudragit microspheres using the spherical crystallization technique, and the effects of drug-related factors on the properties of Eudragit microspheres were investigated. The entrapment of the active compound within the microspheres was highly dependent on the acidic or basic characteristics of the drug. Structural changes were also observed on the microsphere surface prepared at different pH values. Microspheres prepared with slightly and very slightly soluble drugs such as salicylic acid, naproxen, piroxicam, indomethacin, and methylprednisolone indicated controlled-release properties. Generally, drug release from microspheres followed the Fickian diffusion model.
Keywords: SOLVENT EVAPORATION METHOD; ACID